Deep Neural Networks: A Bidirectional Deep Neural Network for Accurate Silicon Color Design (Adv. Mater. 51/2019). Issue 51 (17th December 2019) - Gao, Li; Li, Xiaozhong; Liu, Dianjing; Wang, Lianhui; Yu, Zongfu
Abstract : In article number 1905467, to avoid time‐consuming electromagnetic simulation and an iterative optimization process, Li Gao, Zongfu Yu, and co‐workers report the training of a deep neural network that can perform both forward modeling and inverse design of one million different structural colors. The adoption of a tandem network can solve the nonuniqueness problem in the inverse design process with high efficiency and accuracy.